Pirfenidone: an update on clinical trial data and insights from everyday practice - Kreuter, Michael (European respiratory review, 2014)
Pirfenidone is an orally active, small molecule that inhibits synthesis of profibrotic and inflammatory mediators. It was approved for the treatment of adults with mild-to-moderate idiopathic pulmonary fibrosis in the European Union based on the results of two pivotal phase III, double-blind, randomised, placebo-controlled clinical trials (CAPACITY) demonstrating efficacy and safety, and supported by two Japanese clinical trials (SP2 and SP3). Currently, there is increasing interest in experience with pirfenidone in patients relating to the real-world setting. - Following the publication of the CAPACITY clinical studies, additional analyses have been conducted to provide further support for pirfenidone in clinical practice, including a modified per-protocol analysis of the CAPACITY study population. New data from the RECAP extension study also provided longer term data for pirfenidone and promising continuation rates with treatment. Pirfenidone is also being evaluated in specialist centre cohorts providing important information on real-world efficacy and safety. Increasing experience with pirfenidone in everyday clinical practice is helping to establish \expert guidance on the management of known adverse events, together with practical recommendations, to ensure adherence to treatment so that the possible longer term benefits of pirfenidone treatment in reducing lung function decline can be maximised.